2016
DOI: 10.1016/j.jpowsour.2016.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Exothermic behaviors of mechanically abused lithium-ion batteries with dibenzylamine

Abstract: A thermal-runaway retardant (TRR) of lithium-ion batteries (LIBs), dibenzylamine (DBA), is investigated. In a TRR-modified LIB, DBA can be encapsulated in packages made of inert materials. When the LIB is subjected to mechanical abuse, the packages would be broken apart and the TRR is released. In nail penetration and impact tests, addition of 4 wt% DBA reduces the temperature increase of fully charged LIR-2450 cells by nearly 50%. The influence of TRR packages on the cycling performance of LIBs is negligible.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…A similar trend was presented with the 1 Ah capacity pouch cell by Fang et al, although the values differ as the battery under consideration is different from previously studied [21]. There are few researches which focus on the increase in charge transfer resistance by using thermal runaway retardant (TRR) such as dibenzylamine [18], by using flexible separators, or by using high-viscosity protection films [31]. With decrease of internal resistance, the contribution of heat source from the short circuit increased due to a higher short-circuit current with constant contact resistance (constant size of penetrating element) [31].…”
Section: Effect Of the Location Of The Penetrating Elementsupporting
confidence: 66%
See 1 more Smart Citation
“…A similar trend was presented with the 1 Ah capacity pouch cell by Fang et al, although the values differ as the battery under consideration is different from previously studied [21]. There are few researches which focus on the increase in charge transfer resistance by using thermal runaway retardant (TRR) such as dibenzylamine [18], by using flexible separators, or by using high-viscosity protection films [31]. With decrease of internal resistance, the contribution of heat source from the short circuit increased due to a higher short-circuit current with constant contact resistance (constant size of penetrating element) [31].…”
Section: Effect Of the Location Of The Penetrating Elementsupporting
confidence: 66%
“…Shi et al conducted an experimental study on the exothermic behavior of LIB under mechanical abuse and suggested that dibenzylamine (DBA) could be used to prevent thermal runaway. The authors suggested that under normal conditions DBA does not affect the battery performance, and during mechanical abuse, DBA is released, which increases electrolyte resistivity preventing thermal runaway [18]. Vyroubal et al presented a finite element model of nail penetration into the lithium-ion battery and showed that shorting resistance has a significant influence on the cell electrochemical-thermal process of batteries [19].…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms are thermally triggered, inefficient in severe shorting caused by intense mechanical abuse. To address mechanically induced thermal runway, we investigated mechanically triggered thermalrunaway mitigation methods, e.g., by adding damage homogenizers (DHs) 13 or thermal-runaway retardants (TRRs) 14 in LIB cells. The DH additives could be microparticles of carbon black (CB) or carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…For Lithium Nickel Manganese Cobalt Oxide (NMC) AMs, the onset temperature of thermal runaway is around 170 °C . Other TRM methods include shut‐down separators, damage homogenizers, thermal‐runaway retardants, and deformed current collector…”
Section: Introductionmentioning
confidence: 99%